KAJIAN HUKUM TERHADAP TINDAK PIDANA PERUSAKAN GEDUNG MILIK ORANG LAIN SECARA BERKELOMPOK - I Nyoman Suandika; Ni Luh Sayu Hary Sudewi (Jurnal Ilmiah Raad Kertha, 2021)
The 1945 Constitution of the Republic of Indonesia in Article 1 Paragraph (3) confirms that the State of Indonesia is a state of law. The affirmation of the rule of law implies that every action of the state and citizens must be based on and based on the law. Demonstrations that are destructive in nature can disrupt campus order and security. Demonstrations that end in vandalism often result in fatalities and injuries, both from the protesters and from the security forces at the demonstration, namely campus security units and even police. The reality shows that there are still frequent demonstrations or demonstrations that lead to the destruction of campus facilities, which greatly disturbs the comfort and order in carrying out campus activities. Starting from this reality, several problems arise in this thesis, namely what are the factors that influence the criminal act of destroying other people's buildings which are carried out in groups and what are the legal sanctions for the criminal acts of destroying other people's buildings in groups. The type of research used in this study is a normative legal research type, namely by reviewing or analyzing legal materials from the literature or books and laws and regulations related to the research to be discussed, using the statute approach and the fact approach. The results of the discussion of this thesis are the factors that influence the criminal act of destroying other people's buildings which are carried out in groups, namely environmental factors, social factors, social control factors, and religious factors, as well as provocation factors. Legal sanctions for the criminal act of destroying buildings belonging to other people in groups are regulated in the provisions of Article 408 of the Criminal Code concerning destroying and destroying goods as described in Article 408, which reads that whoever intentionally and unlawfully destroys, damages or renders train buildings unusable. fire, tram, telegraph or electricity, or buildings to stem, divide or distribute water, gas lines, water or channels used for public purposes, is punishable by a maximum imprisonment of 4 (four years).